2019
DOI: 10.1016/j.snb.2018.11.053
|View full text |Cite
|
Sign up to set email alerts
|

Substrate displacement colorimetry for the detection of diarylethylamines

Abstract: In this work, a novel detection assay for the new psychoactive substance (NPS) 2-methoxiphenidine (2-MXP) and other diarylethylamines is introduced. The assay is based on the competitive displacement of dye molecules from molecularly imprinted polymers (MIPs) by the target molecule. The assay was fully characterized by studying the affinity of the MIP for six common dyes, expressed as the binding factor (BF). The results of this study indicate that the mathematical relationship between the BF of a dye and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…The greater complexity of these devices is shown in their mechanisms of action, which are often optical, electro(chemical) or magnetic [ 8 ], but also include other mode of actions—e.g., thermal sensor systems [ 9 , 10 ]. Optical systems include more straightforward UV/Vis or fluorescence sensors, as well as more complex systems using quantum dot and surface-plasmon-resonance technology or even genetically encoded biosensors [ 11 , 12 , 13 , 14 ]. Examples of electro-(chemical) systems range from basic ampere or voltametric systems over graphene-based field-effect-transistors to DNA-annealing-based redox-reporter assays [ 15 , 16 , 17 , 18 ].…”
Section: Researchmentioning
confidence: 99%
“…The greater complexity of these devices is shown in their mechanisms of action, which are often optical, electro(chemical) or magnetic [ 8 ], but also include other mode of actions—e.g., thermal sensor systems [ 9 , 10 ]. Optical systems include more straightforward UV/Vis or fluorescence sensors, as well as more complex systems using quantum dot and surface-plasmon-resonance technology or even genetically encoded biosensors [ 11 , 12 , 13 , 14 ]. Examples of electro-(chemical) systems range from basic ampere or voltametric systems over graphene-based field-effect-transistors to DNA-annealing-based redox-reporter assays [ 15 , 16 , 17 , 18 ].…”
Section: Researchmentioning
confidence: 99%
“…The amount of the dye displaced by amphetamine was not seen to increase past the period of one minute, which could be due to the difference in the binding factor between the dye molecule and amphetamine. It was shown in a previous study (Lowdon et al [ 39 ]) that the difference in the binding affinities of the molecules was one of the driving forces behind the displacement reaction. It has previously been reported that the interaction was not as fast as it has been observed here; however, the difference in the binding factors in this scenario is much greater than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for the synthesis of the optimized MIP followed the method previously reported [ 39 ]. In essence, a mixture of the functional monomer methacrylic acid (MAA, 0.27 mL, 3.1 mmol), functional crosslinker ethylene glycol dimethacrylate (EGDMA, 1.73 mL, 9.2 mmol) and thermal initiator azobisisobutyronitril (AIBN, 50 mg, 0.30 mmol) in 3 mL of dimethyl sulfoxide (DMSO), together with (±) amphetamine hydrochloride (50 mg, 0.29 mmol), was prepared in a 15 mL glass vial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MIP Synthesis : MIP and NIP particles were obtained using the same method described by Lowdon et al Briefly, MIPs were synthetized using methacrylic acid (MAA) as monomer and 2‐MXP as template. A mixture of 1.82 mmol MAA and 0.17 mmol 2‐MXP was dissolved in 3 mL of dimethylsulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%